Cold War Redux?. Issue 4 (4th July 2022) - Crandall, Russell
Abstract: In The Twilight Struggle, diplomatic historian Hal Brands urges readers to revisit Cold War history to gain vital insights and lessons regarding the United States' unfolding geopolitical and ideological competition with Russia and China, which he sees as unfolding in the 'no-man's land between peace and war'. The author does not believe that the Cold War is a perfect facsimile of today's fraught global environment, but the struggles of the twentieth century are nonetheless startlingly similar, not least because the threats of failure, decline and even annihilation are as acute today as they were then. Brands's timely book details the strategies employed by America's Cold Warriors in their contest with the Soviet Union, suggesting that they remain relevant today. The question is whether the United States and the West are willing and able to heed the author's warning and act accordingly.